Development Of Digital Module ‘Kopixplore’ Android-Based On Coffee For Culinary Vocational Students - Fadianisa Aqilah; Lucia Tri Pangesthi; Andika Kuncoro Widagdo; Hidayatun Muyasyaroh (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The implementation of the Merdeka Curriculum, which emphasizes student-centered learning, learner autonomy, the use of technology, and alignment with industry needs, encourages innovation in instructional materials for vocational education in Vocational High Schools (SMK). One such innovation is the development of the KopiXplore digital module, an Android application designed for culinary vocational students, featuring coffee-related materials, available at the following link: https://shorturl.at/JoFIF. This study aims to: (1) produce a KopiXplore digital module based on an Android application for coffee materials, (2) to determine the feasibility of KopiXplore digital module materials and media, and (3) identify students’ responses to the use of the module. This research employed a Research and Development (R&D) approach based on the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The data were collected using questionnaires administered to three material experts, three media experts, and 32 culinary vocational high school students as subjects of a limited trial. The collected data were analyzed using descriptive quantitative techniques, expressed as percentages. The results showed that the KopiXplore digital module achieved a material feasibility score of 99.8%, categorized as very feasible; a media feasibility score of 97%, categorized as very feasible, and a student response score of 85%, categorized as very good. This research makes a tangible contribution to vocational learning by providing digital teaching materials that support the linkage between school learning and the culinary industry’s needs. Based on these results, it can be concluded that the KopiXplore digital module, based on an Android application, is feasible to be used as a digital instructional material for coffee learning for culinary vocational high school students.